The Use of Social Media as a Source of Information on Infant Immunization for Mothers in Surabaya - H. Arviani; S. S. Alamiyah (Nusantara Science and Technology Proceedings)
Research on health literacy in Indonesia is still rare. It is important to know how the behavior of mothers in Surabaya in finding information about the complete basic immunization program. How do they use social media platforms to meet health information needs and how is the health literacy level of mothers. The research question in this study includes how health information seeking behavior of mothers who have babies in Surabaya through social media. What type of social media platform is used by mothers who have babies in Surabaya to get information about the complete basic immunization program? And how mothers who have babies in Surabaya use and apply health information through social media. The theoretical framework used is social media, social media use, health literacy and information seeking behavioral theory. This research is initial research that uses Mixed Methods Research with data collection techniques through questionnaires, focus group discussions, observations, literature studies. The results of this study stated that almost all of the respondents used the internet to find information other than the Kader Posyandu and Pediatricians. The social media platforms commonly used to search for health information are WhatsApp Group (31%), Health-based Applications (22%), Instagram (13%), Facebook (10%), and others (4%).